(untitled) - Nishida, Kitarō (Honolulu, 1973)
A great number of works of art, it is commonly claimed, are aesthetically valuable. Some philosophers have even argued that providing an aesthetically pleasing experience is their only proper function. However, some of these artworks display or invite us to adopt an immoral point of view. Even worse, they even seem to make immoral situations delightful and appealing. The following questions thus arise: Does the alleged immorality of these works count as an aesthetic or artistic defect? Can an immoral movie or novel ever be a great example of its kind? In addition to these concerns related to art evaluation, the connection between various forms of art and morality has been investigated by discussing the capacity of works of art to move us emotionally. More specifically, thinkers from different traditions and ages have remarked that works of art are clearly able, first, to stir our emotions in a particularly effective way, and, second, to invite us to act following certain ideas that have been made appealing by their beauty or other aesthetic qualities. Plato was the first in the Western tradition to evaluate in a systematic way whether, as a consequence of the previous considerations, we should supervise the storytellers who are supposed to educate our youth. Other philosophers, from Aristotle to more recent advocates of the value of the humanities, have argued in favor of the positive role that truly great works of art may have in our moral education. Contemporary philosophers are also interested in the role of imagination in fictional immoral contexts (can we engage with immoral works of art and be justified in so doing?). They are also interested in the role played by art in contributing to our well-being and flourishing as human beings. The great majority of recent works on the topic, however, are focused on an assessment of the arguments in favor or against ethical criticism, with a particular emphasis on the criticism of representational works of art. Other issues at the intersection of art and morality are the concept of the obscene, the value of pornography, and censorship.
Keywords: Nghệ thuật và đạo đức,Art and morals